KAJIAN KADAR TIMBAL PADA RAMBUT PETUGAS OPERATOR STASIUN PENGISIAN BAHAN BAKAR UMUM DI KAWASAN INDUSTRI - Fini Ainun Qolbi Wasdili; Annisa Ulfa Septiana Arisanti; Wikan Mahargyani; Ganthina Sugihartina (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST, 2024)
Increasing population growth, industrialization and the use of motorized vehicles are the factors causing the increase in air pollution. One of the particles contained in the exhaust gas emissions produced is lead. This study was aimed at the operators of the Public Fuel Filling Station in the Industrial Area of West Bandung District who are vulnerable to lead exposure from various pollutant sources. The purpose of this study was to describe the highest and lowest levels of lead accumulated in the hair of gas station operators. The method used is descriptive method. The research sample was taken from respondents who have worked as gas station operators for >1 year. The sample used was 19 gas station operators. Data was collected by filling out a questionnaire followed by laboratory examination. The results showed that 5 people had lead levels exceeding the normal threshold and 14 others had normal lead levels with an average of 13.52 g/g. The highest lead content in hair was 110.75 g/g and the lowest level was -3.50 g/g. With a threshold value of lead levels in hair that is <12Â mg/g. The head of the gas station is advised to apply regulations on the use of appropriate PPE for gas station operators to minimize lead exposure. For further research, it is recommended to monitor lead (Pb) levels with different specimens.   Keywords      : Lead, Hair, Gas Station, Industry, Motor Vehicle